Heads-up! An alert and warning system for phishing emails - Molly Cooper; Yair Levy; Ling Wang; Laurie Dringus (Organizational Cybersecurity Journal, 2021)
Purpose – This study introduces the concept of audiovisual alerts and warnings as a way to reduce phishing susceptibility on mobile devices. Design/methodology/approach – This study has three phases. The first phase included 32 subject matter experts that provided feedback toward a phishing alert and warning system. The second phase included development and a pilot study to validate a phishing alert and warning system prototype. The third phase included delivery of the Phishing Alert and Warning System (PAWSTM mobile app) to 205 participants. This study designed, developed, as well as empirically tested the PAWSTM mobile app that alerted and warned participants to the signs of phishing in emails on mobile devices. Findings – The results of this study indicated audio alerts and visual warnings potentially lower phishing susceptibility in emails. Audiovisual warnings appeared to assist study participants in noticing phishing emails more easily and in less time than without audiovisual warnings. Practical implications – This study's implications to mitigation of phishing emails are key, as it appears that alerts and warnings added to email applications may play a significant role in the reduction of phishing susceptibility. Originality/value – This study extends the existing information security body of knowledge on phishing prevention and awareness by using audiovisual alerts and warnings to email recipients tested in real-life applications.